2D MXenes with antiviral and immunomodulatory properties: A pilot study against SARS-CoV-2. (June 2021) - Unal, Mehmet Altay; Bayrakdar, Fatma; Fusco, Laura; Besbinar, Omur; Shuck, Christopher E.; Yalcin, Süleyman; Erken, Mine Turktas; Ozkul, Aykut; Gurcan, Cansu; Panatli, Oguzhan; Summak, Gokce Yagmur; Gokce, Cemile; et al.
Highlights: Ti3 C2 T x and Mo2 Ti2 C3 T x MXene showed antiviral activity against SARS-CoV-2 as evident by the viability of Vero E6 cells and quantification of viral load following infection. By testing 4 different SARS-Cov-2 viral genotypes, we highlighted the importance of considering viral genotypes and mutations while testing anti-viral activities of any nanomaterial. We revealed the mechanisms of Ti3 C2 T x MXene dependent viral inhibition by proteomic analysis and functional annotation. Ti3 C2 T x MXene, the most potent of the tested materials against SARS-CoV-2 particles, were shown to be not cytotoxic in any peripheral blood mononuclear cell population, demonstrating the high biocompatibility of this material. It is well-known that immune system and cytokine storm play a critical role in COVID-19 progression. Therefore, we used a high-dimensional approach to dissect its effects on 17 distinct immune subpopulations by single cell mass cytometry; Ti3 C2 T x was able to reduce the release of pro-inflammatory cytokines. Graphical Abstract: ga1 Abstract: Two-dimensional transition metal carbides/carbonitrides known as MXenes are rapidly growing as multimodal nanoplatforms in biomedicine. Here, taking SARS-CoV-2 as a model, we explored the antiviral properties and immune-profile of a large panel of four highly stable and well-characterized MXenes - Ti3 C2 Tx, Ta4 C3 T x, Mo2 Ti2 C3 T x and Nb4 C3 T x . To start with antiviral assessment, we first selected and deeply analyzed four different SARS-CoV-2 genotypes, common in most countries and carrying the wild type or mutated spike protein. When inhibition of the viral infection was tested in vitro with four viral clades, Ti3 C2 T x in particular, was able to significantly reduce infection only in SARS-CoV-2/clade GR infected Vero E6 cells. This difference in the antiviral activity, among the four viral particles tested, highlights the importance of considering the viral genotypes and mutations while testing antiviral activity of potential drugs and nanomaterials. Among the other MXenes tested, Mo2 Ti2 C3 T x also showed antiviral properties. Proteomic, functional annotation analysis and comparison to the already published SARS-CoV-2 protein interaction map revealed that MXene-treatment exerts specific inhibitory mechanisms. Envisaging future antiviral MXene-based drug nano-formulations and considering the central importance of the immune response to viral infections, the immune impact of MXenes was evaluated on human primary immune cells by flow cytometry and single-cell mass cytometry on 17 distinct immune subpopulations. Moreover, 40 secreted cytokines were analyzed by Luminex technology. MXene immune profiling revealed i) the excellent bio and immune compatibility of the material, as well as the ability of MXene ii) to inhibit monocytes and iii) to reduce the release of pro-inflammatory cytokines, suggesting an anti-inflammatory effect elicited by MXene. We here report a selection of MXenes and viral SARS-CoV-2 genotypes/mutations, a series of the computational, structural and molecular data depicting deeply the SARS-CoV-2 mechanism of inhibition, as well as high dimensional single-cell immune-MXene profiling. Taken together, our results provide a compendium of knowledge for new developments of MXene-based multi-functioning nanosystems as antivirals and immune-modulators.